DEVELOPMENT OF PSYCHOLOGICAL READINESS OF MILITARY PERSONNEL OF TANK UNITS FOR COMBAT TASK PERFORMANCE - Yurkova, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article presents the results of an experimental study of the development of the psychological readiness of servicemen of tank units for combat tasks performance. The formative part of the experimental study was carried out by implementing the program aimed at developing the components of psychological readiness (cognitive, motivational, emotional-volitional, functional and individual psychological qualities). The experiment was conducted in the period from 2021 to 2022. After applying the method of mathematical statistics (non-parametric Mann-Whitney U-tests), the statistically significant changes in indicators were revealed, that occurred in those servicemen of tank units with whom the formative program was conducted. The peculiarities of statistical changes in each of the components were revealed and their interpretation was carried out. It was found that the main workload of the tank crewman’s professional activity falls on areas directly related to the implementation of special techniques, skills and methods of action, working out the specific conditions of military personnel, which demonstrated positive statistically significant indicators during the course of the program. A comparative analysis of the diagnostic results of the control and experimental groups after conducting the formative experiment testifies the effectiveness of the author’s program, which expands the system of professional knowledge, strengthens motivation, develops important professional skills and the personal construct of the tank crewman. Thus, the proposed measures are aimed at developing the criteria of each of the components of psychological readiness and collectively form personal psychological readiness, which, in turn, is the basis for the group psychological readiness of the tank unit. The result of the implementation of the program is the formation of new ideas about psychological readiness as an integral manifestation of a professional, which in turn encourages self-development.